2016
DOI: 10.1007/s00439-016-1661-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in CSNK2A1 are associated with neurodevelopmental abnormalities and dysmorphic features

Abstract: Whole exome sequencing (WES) can be used to efficiently identify de novo genetic variants associated with genetically heterogeneous conditions including intellectual disabilities. We have performed WES for 4102 (1847 female; 2255 male) intellectual disability/developmental delay cases and we report five patients with a neurodevelopmental disorder associated with developmental delay, intellectual disability, behavioral problems, hypotonia, speech problems, microcephaly, pachygyria and dysmorphic features in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(115 citation statements)
references
References 21 publications
7
106
2
Order By: Relevance
“…Taking this into account, and given the fact that CSNK2A1 is located at chromosome 20 and not at the X-chromosome, it is unlikely that variable X-chromosome inactivation contributes to the phenotypic variability between individuals, as suggested before. 7 We included clinical photographs from Subjects…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking this into account, and given the fact that CSNK2A1 is located at chromosome 20 and not at the X-chromosome, it is unlikely that variable X-chromosome inactivation contributes to the phenotypic variability between individuals, as suggested before. 7 We included clinical photographs from Subjects…”
Section: Discussionmentioning
confidence: 99%
“…10 Okur et al suggested that X-chromosome and X-inactivation are possibly involved in pathogenesis of CSNK2A1 variants, because only females were identified. 7 We report an addition of 6 boys and 2 girls with de novo germline variants in CSNK2A1. All individuals presented with neurodevelopmental and multisystemic abnormalities.…”
Section: Introductionmentioning
confidence: 85%
“…CSNK2A1 variants were first reported as causative of an intellectual disability and a range of medical problems in 2016: this report led to the eponymous designation of the condition as the Okur–Chung neurodevelopmental syndrome (Okur et al, ). Subsequently an additional patient with a de novo CSNK2A1 missense variant and an intellectual disability has been reported (Trinh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date six patients with CSNK2A1 variants have been reported. An initial series included five patients with de novo heterozygous CSNK2A1 missense or consensus splice site variants and variable combinations of intellectual disability, hypotonia, speech problems, gastrointestinal problems, immune dysfunction, pachygyria, and dysmorphic facial features (Okur et al, ). Subsequent to this report, the condition was eponymously named the Okur–Chung neurodevelopmental syndrome (OMIM 617062).…”
Section: Introductionmentioning
confidence: 99%
“…Okur‐Chung neurodevelopmental syndrome (OCNS, MIM#617062) is a rare autosomal dominant syndrome first described in 2016 by Okur et al related to de novo CSNK2A1 mutations (Okur et al, ). In the following years, seven additional publications have expanded the phenotype showing a high interpatient variability (Duan et al, ).…”
Section: Introductionmentioning
confidence: 99%